Physical and Mental Health Status of Tribal People in Odisha: A Systematic Literature Review - Behera N.; Pandey K.; Shankar S. (My University, 2025)
Background: India has the world’s second-largest tribal population, making it imperative to study and understand the health issues of tribal communities. However, the extent of physical and mental health issues is relatively unknown in the country, especially in the tribal-dominated state of Odisha. With this idea, we systematically reviewed the studies associated with the physical and mental health conditions of Tribals in Odisha. Objective: The present systematic review aims to analyze research articles associated with physical and mental health and provide a comprehensive health status of tribal people in Odisha. Design: Systematic literature review (SLR). Data Sources: The studies were searched through the 10 major scientific databases (ProQuest, Google Scholar, Scopus, PubMed, CENTRAL, DARE, Embase, PsycINFO, Medline, and CINAHL) with specific journal websites. Papers published from 2010 to the present in English with peer-reviewed journals were considered for eligibility. Review Methods: Adhering to preferred reporting items for systematic reviews (PRISMA), twenty-five articles that met inclusion criteria were extracted and assessed the risk of bias by the authors. Results: The study analyzed 25 papers on tribal communities in Odisha, revealing various physical and mental health issues such as TB, malaria, infestations, and infections. Low socio-economic conditions, lack of education, societal customs, poor hygiene, malnutrition, unsanitary living conditions, and food insecurity are the causes of prone to disease. For treatment, they use different types of traditional methods such as wild-ant chutney for cough, Amar poi leaves for diarrhea, and Ganagasiuli leaves juice for malaria and fever. Tribal communities also suffer from different types of mental health issues like stress, depression, and bipolar disorder. Conclusion: To change perceptions, address superstitions, and enhance mental and physical health in Odisha’s tribal communities, the government should prioritize education, implement community therapy, and devise comprehensive socioeconomic development plans. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.